Estudio comparativo de casos de intoxicaciones por insecticidas organofosforados en diferentes zonas de Costa Rica - Ingianna A., Josefina (1983)
336 cases of organophosphorous poisoning from case records of hospitals in Costa Rica between 1 97 2 and 1978 were classified in four categories according to signs and symptoms: 8% latent; 25.9% mild; 43.8% moderate and 22.3% severe. Eighteen of the total patients died during hospitalization.Suicidal ingestion was the principal cause of severe and latent poisoning, especially in urban areas. followed by occupational poisoning in agricultural workers in mild and moderate cases. Occupational poisoning was common in men; in women it was attempted suicide and in children accidental poisoning. Under 40 years of age, the main cause was suicidal ingestion among both men and women, and occupational poisoning after 40 years of age.After discharge from the hospital, 19.6% of the total poisoned patients were referred to psychiatric treatment; 22.7% and 18.2% had had mental and alcoholic problems, respectively, prior to poisoning. Attempted suicide was the principal cause of poisoning in 86.4% of these patients, indicating emotional instability. In this study, the incidence in psychiatric consultation after discharge from the hospital is not indicative of a relationship between mental disorders and acute insecticide poisoning.In 42.6% and in 22% of the deceased patients pralidoxime (PAM) and atropine respectively, were not administered as antidotes in the emergency room. Aminophylline and skeletal muscle relaxants among other contraindicated drugs were administered as part of the treatment in these deceased patients. The consequences of this misguided treatment are questioned.